Etiology of urinary tract infection and drug resistance cases of uropathogenes - Bhatt, CP; Shrestha, B; Khadka, S; Swar, S; Shah, B; Pun, K (Journal of Kathmandu Medical College, 2013)
Background: Multidrug resistant bacterial isolates have been frequently reported from different parts of the world as emerging treatment problem. Objectives: The study was conducted to find out etiology of urinary tract infection and drug resistance trend among clinical pathogens in urinary tract. Methods: Mid-stream urine samples from patients suspected of urinary tract infection were collected for routine culture and antibiotic susceptibility testing and were processed according to the standard laboratory methods. Results: In this study 41.7% urine samples showed significant bacterial growth. Gram negative bacteria were the predominant organisms. Among them Escherichia coli was the predominant isolate (85.1%) whereas Enterococcus faecalis (40.6%), was the major Gram positive isolate. Among culture positive cases organisms were isolated in highest frequency (29.5%) in the age group 21 to 30 years. Urinary tract infections were found more common in females (61.1%) than in males (38.9%). Nitrofurantoin (82.2%) and Ofloxacin (57.8%) were found to be the most effective drugs against Gram negative organisms, whereas for Gram positive organisms, Nitrofurantoin (87.5%) and Gentamycin (78.1%) were found to be the most effective drugs. Escherichia coli was found sensitive to Nitrofurantoin (89.3%) followed by Ofl oxacin (63.3%). Enterococcus faecalis was most susceptible to Nitrofurantion (92.3%) followed by Cotrimoxazole (76.9%). Conclusion: In this study, among the participants 41.7% had culture positive urinary tract infection. Drug resistance was found to be high in both Gram negative and Gram positive organisms. The high prevalence of drug resistance among urinary tract infection patients calls for the need of judicious measures for control of this infection and knowledge of patterns of resistance helps in deciding empirical therapy for urinary tract infection. DOI: http://dx.doi.org/10.3126/jkmc.v1i2.8150 Journal of Kathmandu Medical College, Vol. 1, No. 2, Oct.-Dec., 2012: 114-120